Unintended affinities : Nineteenth-century German and Polish historians on the Holy Roman Empire and Polish-Lithuanian Commonwealth - Kożuchowski, Adam, 1979- (Series in Russian and East European studies., 2019)
Unintended Affinities' examines the ways in which German and Polish historians of the nineteenth-century regarded the Holy Roman Empire and the Polish-Lithuanian Commonwealth. 0The book parallels how historians approached the old Reich and the Commonwealth within the framework of their national history. Ko?uchowski analyzes how German and Polish nationalistic historians, who played central roles in propagandizing a glorious past that justified a centralized modern state, struggled with how to portray the very decentralized and multi-ethnic empires that preceded their time.